1997
DOI: 10.1002/bjs.1800840329
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant intraoperative photodynamic therapy in experimental colorectal cancer using a new photosensitizer

Abstract: AIOPDT using either Photofrin or m-THPC was equally effective in reducing local recurrence in this model. Since treatment time with m-THPC was only 25 s compared with 11 min with Photofrin, the use of the former new photosensitizer increases the practicality of AIOPDT and could enable the laser to be replaced with cheaper, less intense light sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It can be prepared as a chemically pure compound, it shows enrichment in tumor versus normal tissue and has an absorption maximum at 650 nm, redshifted compared to HpD which means deeper light penetration. In addition, m THPC requires smaller quantities for administration, shorter treatment times and a lower light dose to achieve the desired PDT response (45).…”
Section: Chemistry and Development Of Temoporfinmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be prepared as a chemically pure compound, it shows enrichment in tumor versus normal tissue and has an absorption maximum at 650 nm, redshifted compared to HpD which means deeper light penetration. In addition, m THPC requires smaller quantities for administration, shorter treatment times and a lower light dose to achieve the desired PDT response (45).…”
Section: Chemistry and Development Of Temoporfinmentioning
confidence: 99%
“…In another study with murine colorectal cancer implanted mice it was shown that the highest tumor:tissue ratios after 4 days were found for the small intestine, liver and skeletal muscle (134). This animal model was used as a general test bed for PDT assessment (271) and for AIOPDT (45). A study of healthy hamsters showed highest drug levels in the gastric and duodenal mucosa and acinar pancreas after 2–4 days (272).…”
mentioning
confidence: 99%
“…In view of the frequency of colorectal cancer in the West it surprising that there are relatively few reports of photodynamic therapy for tumours at this site 94 , . 145 –159 This may be due to surgical treatment having a better outcome than for many other gastrointestinal tumours and the recognition that laser therapy and stents alone can be effective 99 , . 160 , 161 What little research there is indicates encouraging response rates and symptomatic relief after photodynamic therapy.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…In an animal model of recurrent colorectal cancer, Abulafi et al. found that in animals, mTHPC was as effective as Photofrin but its use significantly reduced the treatment time 159 …”
Section: Clinical Applicationmentioning
confidence: 99%
“…These deliberations are under current consideration by the American Joint Committee on Cancer with a view to publication. A number of items concerning management of patients could have been the subject of contributions: carcinoembryonic antigen [5]; photodynamic therapy [6,7]; local resection by micro-endoscopic techniques [8]; intraportal 5-fluorouracil and heparin as adjuvant therapy [9,10]; clinical management of obstruction [11,12]; and developments in intra-operative orthograde gut lavage [13] …”
mentioning
confidence: 99%